Compared morphology of the immatures of males of two urban ant species of camponotus - Solis, Daniel Russ [UNESP]; Fox, Eduardo Gonalves Paterson; Rossi, Mnica Lanzoni; Bueno, Odair Correa [UNESP] (Oxford University Press (OUP), 2012)
The immatures of males of two species of Camponotus ants (Hymenoptera: Formicidae) are described and compared by light and electron microscopy. The numbers of larval instars were determined: Camponotus rufipes Fabricius (Hymenoptera: Formicidae) have four instars; and Camponotus vittatus Forel have three. Male larvae of the two species are similar to previously described Camponotus larvae, sharing the following traits: basic shape of body and mandible, presence of 'chiloscleres', 'praesaepium' (some specimens), labial pseudopalps, and ten pairs of spiracles. However, larvae of the two species can be separated by bodily dimensions and based on their hair number and types. Worker larvae of C. vittatus previously described are extensively similar to male larvae, with only a few inconspicuous differences that may result from intraspecific variation or sexual differences.
Keywords: Formicidae; Formicinae; larvae; Myrmothrix; Tanaemyrmex; Camponotus; Camponotus rufipes; Camponotus vittatus; Hymenoptera; animal; ant; classification; comparative study; cytology; growth, development and aging; histology; insect; larva; male; oocyte; sexual development; ultrastructure; Animals; Ants; Larva; Male; Ovum; Pupa; Sex Characteristics